Firm Productivity and Immigrant-Native Earnings Disparity - Olof Aslund; Cristina Bratu; Stefano Lombardi; Anna Thoresson (Institute of Labor Economics (IZA), 2021)
We study the role of firm productivity in explaining earnings disparities between immigrants and natives using population-wide matched employer-employee data from Sweden. We find substantial earnings returns to working in firms with higher persistent productivity, with greater gains for immigrants from non-Western countries. Moreover, the pass-through of within-firm productivity variation to earnings is stronger for immigrants in low-productive, immigrant-dense firms. But immigrant workers are underrepresented in high-productive firms and less likely to move up the productivity distribution. Thus, sorting into less productive firms decreases earnings in poor-performing immigrant groups that would gain the most from working in high-productive firms.
Keywords: J15; J31; J62; 330; firm productivity; immigrant-native earnings gaps; wage inequality